Variational treatment of a vibrating LiNbO3-based rectangular hybrid structure: the developing of a functional for computing surface-load configurations - POLOVINA, Oleksiy I.; KURYLIUK, Vasyl V.; KOROTCHENKOV, Oleg A. (Archives of Acoustics, 2009)
Electrically-excited electroelastic extensional vibrations of an arbitrarily cut three-dimensional piezocrystal resonator are analyzed variationally. A set of trigonometric trial functions applicable to a waveguide behavior of the resonator partly covered by metal electrodes is proposed. The dependence of the content of the vibration modes sustained by the resonator on the electrode configuration is found. The frequency spectra taken in 128o-Y-rotated LiNbO3 rectangular plates exhibit a good conformity with the computed resonator eigenfrequencies.